Analysis of The Need for an Ethno-Steam-Based Learning Module to Improve Narrative Text Writing Skills - Umrotullatifah, Nurul; Riyadi, Arie Rakhmat; Heryani, Rina; Afifah (International Conference on Elementary Education, 2025)
This research is motivated by the low ability of fourth-grade elementary school students to write narrative texts. Many students still have difficulty expressing ideas or themes, structuring a coherent flow, determining characters and settings, and choosing language styles that comply with Indonesian grammar rules. The learning activity process applies a conventional learning model with the lecture method, and the teaching materials used by the teacher are limited to school textbooks. This condition is one of the causes and obstacles for students in developing their imagination and creativity during the writing process. Based on these issues, this research aims to analyze the need for an Ethno-Steam-based learning module to improve the narrative text writing skills of fourth-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE method. However, this research is only limited to the Analysis stage. Research data was obtained from interviews, analysis of teaching material documents, and initial observations of learning implementation. The analysis results show that a learning module with an Ethno-Steam approach is highly needed to improve the narrative text writing ability of fourth-grade elementary school students.